2016
DOI: 10.1590/abd1806-4841.20165478
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated cryptococcosis with cutaneous involvement in an immunocompetent patient

Abstract: Cryptococcosis is a fungal infection of opportunistic behavior that is unusual in immunocompetent patients. We report a rare case of disseminated cryptococcosis with cutaneous involvement in an immunocompetent individual. During hospitalization, Cryptococcus gattii was isolated from skin lesions, lung and spinal fluid. The diagnosis of disseminated cryptococcosis was confirmed and treatment was established. The patient showed improvement. Due to the probable clinical severity of the disease and the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
1
0
3
Order By: Relevance
“…In a recent review of pooled cases of cryptococcosis in HIV-negative patients on renal dialysis, the authors found 18 cases between 1985 and 2016 [3]. Most of these were on peritoneal dialysis and only one had cutaneous lesions [5].…”
Section: Figure 2 Dermal Granulomatous Structures (Hematoxylin-eosin ...mentioning
confidence: 99%
“…In a recent review of pooled cases of cryptococcosis in HIV-negative patients on renal dialysis, the authors found 18 cases between 1985 and 2016 [3]. Most of these were on peritoneal dialysis and only one had cutaneous lesions [5].…”
Section: Figure 2 Dermal Granulomatous Structures (Hematoxylin-eosin ...mentioning
confidence: 99%
“…A forma mais frequentemente de transmissão das infecções criptocócicas ocorre pela inalação de propágulos de leveduras veiculadas pela corrente de ar no ambiente 1 . Deste modo, pode ocorrer acometimento pulmonar sintomático ou assintomático seguido de uma disseminação linfática ou hematogênica para o sistema nervoso central (SNC), pele, olho, ou até mesmo para órgãos do aparelho reprodutor masculino, como próstata (KAWAMOTO et al, 2017;SETIANINGRUM et al, 2018;SACHT et al, 2016;ATHERTON et al, 2018;SHAH et al, 2012). Outras vias de transmissão e consequente disseminação são descritos em raros casos, como uma forma rara de transmissão transplacentária, além da inoculação das leveduras em traumatismos cutâneos, determinado lesões primárias na pele (HURTADO et al, 2016;TABASSUM et al, 2013).…”
Section: Fábio Silvestre Ataidesunclassified
“…Virginia Velasco-Tamariz 1 , Raquel Aragón-Miguel 1 , Elena Gutiérrez-Solís 2 , Mónica Milla-Castellanos 2 , Francisco López-Medrano 3 , Laura Corbella-Vazquez 3 , Raúl Recio-Martínez 4 , Alfredo Pérez-Rivilla 4 , José Luis Rodríguez-Peralto 5 , Pablo Luis Ortiz-Romero 1 , Carlos Zarco-Olivo 1…”
unclassified
“…In einem kürzlich erschienenen Review über gepoolte Kryptokokkose-Fälle bei HIV-negativen Patienten bei der Nierendialyse fanden die Autoren 18 Fälle zwischen 1985 und 2016 [3]. Die Mehrzahl dieser Patienten erhielt eine Peritonealdialyse und nur einer wies Hautveränderungen auf [5].…”
unclassified